2021
DOI: 10.1038/s41598-021-98734-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ondansetron on reducing ICU mortality in patients with acute kidney injury

Abstract: The purpose of this study is to identify medications with potentially beneficial effects on decreasing mortality in patients with acute kidney injury (AKI) while in the intensive care unit (ICU). We used logistic regression to investigate associations between medications received and ICU mortality in patients with AKI in the MIMIC III database. Drugs associated with reduced mortality were then validated using the eICU database. Propensity score matching (PSM) was used for matching the patients’ baseline severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Importantly, potentially favourable effects of OND on reduced in-hospital mortality in acute kidney injury (AKI) patients in the ICU were reported depending on the MIMIC-III database, the eICU database and the MIMIC-IV database. Based on the comparison of gene expression signatures, the latest study illustrated that the advantageous effect of OND might be elicited through the NF-KB pathway and JAK-STAT pathway [ 6 , 7 ]. A recent pharmacoepidemiology study reported that OND was also associated with a significant decrease in 90-day mortality on the High-Density Intensive Care (HiDenIC-15) database containing intensive care data for 13 hospitals across Western Pennsylvania [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, potentially favourable effects of OND on reduced in-hospital mortality in acute kidney injury (AKI) patients in the ICU were reported depending on the MIMIC-III database, the eICU database and the MIMIC-IV database. Based on the comparison of gene expression signatures, the latest study illustrated that the advantageous effect of OND might be elicited through the NF-KB pathway and JAK-STAT pathway [ 6 , 7 ]. A recent pharmacoepidemiology study reported that OND was also associated with a significant decrease in 90-day mortality on the High-Density Intensive Care (HiDenIC-15) database containing intensive care data for 13 hospitals across Western Pennsylvania [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the latest study found that OND could be used to decrease mortality in the coronavirus disease 2019(COVID-19) inpatients [ 4 ]. In addition, OND has been illustrated the potentially pleiotropic effect, including neuroprotection [ 5 ], renal protection [ 6 , 7 ], and anticoagulation [ 8 , 9 ]. However, research on the survival benefit of initial use of OND, particularly in the critically ill, is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is similar to that of three other retrospective cohort studies that investigated critically ills patients with AKI and demonstrated that patients who received ondansetron had significantly lower ICU mortality, in-hospital mortality, and 90-day mortality, respectively ( 17 19 ). Additionally, the genes of 5-HT3 receptor were reported to be upregulated in AKI kidneys, and a molecular mechanism study by gene expression signatures demonstrated that the NF-KB and JAK-STAT pathways might be involved in the potential therapeutic effect of ondansetron in critically ill patients complicated by AKI ( 18 ). These findings suggest the possibility of the 5-HT3 receptor as a therapeutic target for the treatment of AKI patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, a recent pharmacoepidemiologic study has identified an association between ondansetron use and a decrease in the risk for acute kidney injury (AKI). 12 5-HT3 antagonists have also been found to be nephroprotective in animal models. 13 Anti-emetics are generally metabolized through conjugation and hepatic routes, and it is important to further explore the role they play on renal function since anti-emetics are often administered despite compromised renal function because of their relative safety.…”
Section: Introductionmentioning
confidence: 99%